Anthropogenic Habitat Loss and Fragmentation May Alter Coevolutionary Progress as Examined in a Brood Parasitism Model - Wei Wang; Timothy Van Deelen; Fuwen Wei; Sheng Li; Luping Wang (Ecology and Evolution)
ABSTRACT Habitat loss and fragmentation (HLF) resulting from anthropogenic disturbances is one of the greatest threats to numerous threatened taxa facing extinction risks. HLF may devastate biodiversity through various pathways such as restricting animal movement and gene flow, reducing opportunities for species to expand or shift their ranges and thus optimizing habitat use, and directly causing population decline and range contraction. Despite these well‐documented impacts, the effects of HLF on the coevolutionary processes between coexisting species are rarely examined. In this study, we constructed a cuckoo–host brood parasitism model to explore how HLF of varied degrees may affect the cuckoo–host population dynamics through stochastic and reinforcement simulations. The results, validated with empirical data, revealed that severe HLF significantly increases the cuckoo's extinction risk compared to moderate HLF. Furthermore, severe HLF narrows the range of host rejection rates that allow cuckoo populations to persist under natural conditions. These findings suggest that severe HLF, typically driven by human activities and anthropogenic land use change, may not only directly increase the extinction risk of specific species but also disrupt the coevolutionary interactions, posing more severe ecological consequences than previously anticipated.